2014
DOI: 10.1097/bcr.0b013e31828a493f
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nosocomial Burn Wound Infection Caused by Multidrug Resistant Acinetobacter baumannii

Abstract: Acinetobacter baumannii infections in burn patients may lead to delays in wound healing, graft losses, and development of sepsis. Determining the risk factors for multidrug resistant A. baumannii (MDR-AB) infections is essential for infection control. In the present study, the authors aimed to evaluate risk factors for wound infections caused by A. baumannii in burn patients. The study was conducted at Dicle University Hospital Burn Center, from April 2011 to July 2012, to investigate the risk factors for MDR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
2
35
0
2
Order By: Relevance
“…P. aeruginosa was the most common PDR-bacteria followed by MRSA and A.baumannii. These results are similar with many previous studies 5, [45][46][47] . Biofilm formation by microorganisms is one of the most important mechanisms in antimicrobials resistant, consisting of the irreversible assemblage of bacterial cells associated with a surface and enclosed in matrix of polysaccharides material 48 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…P. aeruginosa was the most common PDR-bacteria followed by MRSA and A.baumannii. These results are similar with many previous studies 5, [45][46][47] . Biofilm formation by microorganisms is one of the most important mechanisms in antimicrobials resistant, consisting of the irreversible assemblage of bacterial cells associated with a surface and enclosed in matrix of polysaccharides material 48 .…”
Section: Discussionsupporting
confidence: 83%
“…The overuse and unsuitability of different antimicrobials to treat burn infections has led to the emergence of new MDR, XDR and PDR-bacterial strains that are able to resistant a wide range of many antimicrobials such as aminoglycosides, beta-lactams, cephalosporins, streptomycin and tetracycline 49,50 . Burn infection in hospitalized patients caused by MDR, XDR and PDR-gram negative and gram positive bacteria such as; P. aeruginosa, K. pneumoniae, MRSA, MSSA and A.baumannii may lead to delays in burn healing, graft lose, as well as development of sepsis and death; therefore, determination of the risk factors for these pathogens infections is essential for infection control 47 . The results of this study showed that P. aeruginosa and K. pneumoniae were the most common ESBLproducing gram negative bacteria followed by A.baumannii and E.coli while there was no any strain of ESBL-S.typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that subjects in this study belonged to a young and homogeneous group, of particular interest to us was the influence of both burn severity and time factor on the types of microbial isolates. Several multivariate analyses of prospective or retrospective studies have revealed that the degree of burn wounds was a major risk factor for microbial colonization and infection [1,5,7,26]. Compared to ≤19% of TBSA, patients with greater than 20% of TBSA were more than twice (RR 2.09-2.41) likely to be infected at a rate that was five times faster [7].…”
Section: Main Risk Factors For Microbial Colonization and Infectionmentioning
confidence: 99%
“…Hastane kaynaklı Acinetobacter infeksiyonları genellikle geç edinilmektedir ve çeşitli çalışmalarda, yatış süresinin daha uzun olduğu saptanmıştır (15,16). Sunulan çalışmada da, tek değişkenli analizde, yatış süresi olgu grubunda kontrol gruplarına göre daha uzun bulunmuştur (p=0.005).…”
Section: İrdelemeunclassified